2021
DOI: 10.3390/pharmaceutics13070933
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Control of Drug Release from Complex Immediate Release Formulations

Abstract: The kinetics of water transport into tablets, and how it can be controlled by the formulation as well as the tablet microstructure, are of central importance in order to design and control the dissolution and drug release process, especially for immediate release tablets. This research employed terahertz pulsed imaging to measure the process of water penetrating through tablets using a flow cell. Tablets were prepared over a range of porosity between 10% to 20%. The formulations consist of two drugs (MK-8408: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Dong et al reported an inhibition of water penetration and hence lower swelling of tablets containing a solid dispersion based on HPMC due to the formation of a gel layer. High amounts of MCC promote tablet hydration, as the material swells more rapidly and no gelling occurs ( Dong et al, 2021 ). This might be in good agreement with the comparable behaviour of the investigated tablet formulations containing Kollidon VA64 and MCC displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dong et al reported an inhibition of water penetration and hence lower swelling of tablets containing a solid dispersion based on HPMC due to the formation of a gel layer. High amounts of MCC promote tablet hydration, as the material swells more rapidly and no gelling occurs ( Dong et al, 2021 ). This might be in good agreement with the comparable behaviour of the investigated tablet formulations containing Kollidon VA64 and MCC displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dong and co-workers investigated water transport into immediate-release tablets of varying formulations and microstructures [4]. With these types of tablets, water transport is of utmost importance to control drug release and tablet disintegration.…”
mentioning
confidence: 99%